Electrospun silk–collagen scaffolds and BMP-13 for ligament and tendon repair and regeneration. (18th January 2018) - Maghdouri-White, Yas; Petrova, Stella; Sori, Nardos; Polk, Seth; Wriggers, Hilary; Ogle, Rebecca; Ogle, Roy; Francis, Michael
Abstract: Regenerative ligament and tendon repair scaffolds have been highly researched, yet few match the mechanical properties of native tissue, while fewer drugs have been explored for enhancing cell infiltration into the damaged tissue. Here a nanofiber scaffold of silk fibroin (SF)–collagen blend is explored as a biologically enhanced matrix, along with a therapeutic agent (bone morphogenetic protein-13, [BMP-13]) for connective tissue regeneration. SF and collagen were blended and electrospun to form fibrous scaffolds with 1.15 ± 0.08 μ m diameter fibers. These scaffolds were crosslinked with either methanol or ethanol. Crosslinking with methanol resulted in significantly higher mechanical strength compared to ethanol treated scaffolds (2.92 ± 0.21 MPa versus 1.13 ± 0.08 MPa, respectively). Adipose-derived stem cells showed robust cell attachment and proliferation on SF–collagen scaffolds, with confocal imaging suggesting cellular alignment and spreading. BMP-13 growth factor is further shown to promote cell migration into SF–collagen scaffolds. In all, electrospun SF with telocollagen produces a regenerative matrix with enhanced tensile strength. BMP-13 improves cellular infiltration into electrospun SF–collagen scaffolds and may prove a potent chemotactic agent for enhancing ligament and tendon repair.